Permohonan Pembatalan Pernikahan Karena Kebohongan dan Penipuan: Studi Kasus Penetapan Nomor 3572/Pdt.G/2023/PA.Ckr - Atmadianti, Sri; Rizal, Mhd. (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This study aimed to analyze the case facts of a marriage annulment application contained in Decree Number 3572/Pdt.G/2023/PA.Ckr, the causes of marriage annulment and its legal consequences. This research employed a normative legal research method with a comparative approach. The collected legal materials were analyzed qualitatively to describe the problem and answer the research objectives. The results showed that the marriage annulment application was based on solid grounds according to Law Number 1 of 1974 and the Compilation of Islamic Law. A series of lies and frauds were committed by the Respondent to the Applicant, ranging from concealing his marital status and child, falsifying the date of marriage, to providing a fake gold dowry. Nevertheless, the Applicant chose to withdraw her application and maintain her marriage. This study also reveals that a marriage can be annulled if the parties do not fulfill the pillars and conditions of marriage, with the legal consequence of severing the marital relationship. However, the law provides special protection for children born from an annulled marriage, where they are still considered legitimate children and have inheritance rights from both parents. The fundamental difference between marriage annulment and divorce lies in two crucial aspects: the wife is not entitled to iddah maintenance, and joint property is returned to its original state. Therefore, it is recommended that the Head of the Religious Affairs Office improve premarital counselling programs, Religious Court judges adhere to the principles of justice and wisdom, married couples prioritize honesty and communication, and religious figures actively provide guidance and counselling to prevent disputes that lead to marriage annulment applications.